STUDI RUANG TERBUKA HIJAU DI SEMPADAN SUNGAI CISADANE KELURAHAN CILENGGANG, KECAMATAN SERPONG, KOTA TANGERANG SELATAN - Elisabeth Gabriela Van Der Linde; Priyendiswara Agustina Bella (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
The City of Tangerang Selatan is an independent city which currently has a spatial planning objective as a service center for education, housing, trade and services. Green open space can be used as a guarantor for increasing land value, for adding value to the urban environment, for providing natural tourism spaces, for maintaining historical aspects, for providing spaces for community interaction, etc., and most importantly, for creating harmonious and balanced spaces between built and unbuilt areas. However, with the rapidly increasing population growth in the development of South Tangerang City, the area with the green open space function has decreased and has not yet reached 20% of the area of ​​South Tangerang City. With the arrangement of green open space at the study location, it is known that there are potential contributors to green open space in the City of South Tangerang as a fulfillment of the need for public open space by utilizing green open space on the border of the Cisadane River, Cilenggang Village, Serpong District, South Tangerang City, but still with due regard policies that apply in order to remain in accordance with its function and create an optimal arrangement. Keywords:  green open space, borders, rivers, space requirements Abstrak Kota Tangerang Selatan adalah kota mandiri yang memeiliki tujuan penataan ruang menjadi pusat pelayan bagi pendidikan, perumahan, serta perdagangan dan jasa. Ruang Terbuka Hijau bisa dijadikan sebagai pemberi nilai tambah bagi lingkungan kota, sebagai penambah jaminan peningkatan nilai tanah, sebagai penyediaan ruang untuk wisata alam, pemertahanan aspek historis, penyedia ruang interaksi masyarakat dll, serta yang terpenting dapat menjadi ruang yang seimbang serta serasi anytara area terbangun dan yang tidak. Namun dengan pertumbuhan penduduk yang meningkat pesat serta pembangunan di Kota Tangerang Selatan besar, menjadikan kawasan ruang terbuka hijau di dalamnya menurun dan belum mencapai 20% dari luas Kota Tangerang Selatan. Dengan adanya penataan ruang terbuka hijau pada lokasi studi, diketahui bahwa adanya potensi penyumbang ruang terbuka hijau di Kota Tangerang Selatan menjadi pemenuh kebutuhan ruang RTH publik dengan memanfaatkan ruang terbuka hijau di sempadan sungai cisadane Kelurahan Cilenggang, Kecamatan Serpong Kota tangerang Selatan, namun tetap dengan memperhatikan kebijakan yang berlaku agar tetap sesuai dengan fungsinya dan menjadikan penataan yang optimal.